2014
DOI: 10.1088/2041-8205/784/2/l39
|View full text |Cite
|
Sign up to set email alerts
|

Intensity Enhancement of O Vi Ultraviolet Emission Lines in Solar Spectra Due to Opacity

Abstract: Opacity is a property of many plasmas, and it is normally expected that if an emission line in a plasma becomes optically thick, its intensity ratio to that of another transition that remains optically thin should decrease. However, radiative transfer calculations undertaken both by ourselves and others predict that under certain conditions the intensity ratio of an optically thick to thin line can show an increase over the optically thin value, indicating an enhancement in the former. These conditions include… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Values such as this has been observed before, for example with Skylab data by , where values have been found which are 1.5 at 2 ′′ above the solar limb. More recent work by Keenan et al (2014) has shown for the first time that in the solar case, that this ratio can change in both directions as the result of opacity.…”
Section: Characterising a Single Blobmentioning
confidence: 93%
“…Values such as this has been observed before, for example with Skylab data by , where values have been found which are 1.5 at 2 ′′ above the solar limb. More recent work by Keenan et al (2014) has shown for the first time that in the solar case, that this ratio can change in both directions as the result of opacity.…”
Section: Characterising a Single Blobmentioning
confidence: 93%
“…Therefore, the need arises of accounting for the angular dependence of the spectral distribution which plays directly into experimental design considerations and spectral analysis. This effect has previously been observed in astrophysical and laboratory plasmas 22,23 , and several methods have been proposed to diagnose the geometry of astrophysical bodies by studying it 18,24 .…”
Section: Introductionmentioning
confidence: 65%
“…Therefore, for non-spherical plasmas, the enhancement of optically thick lines depends on the position of the observer with respect to the plasma. This effect has been observed in astrophysical plasmas [45] and has applications to charaterizing the geometry of astrophysical bodies from their line ratios [42,46]. However, to our knowledge, it has never been used for density measurements in laboratory plasmas (although a potential experiment to observe these effects was proposed by Mancini et al [47]).…”
Section: Introductionmentioning
confidence: 93%